Perceptions of shoppers on two nearby shopping centers [electronic resource] - Wee, Zhao Yuan, 1987-, author (2011)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2011